Technology and the gendering of music education - Armstrong, Victoria (Farnham, Surrey, England ; Burlington, VT : Ashgate, 2011)
"This book is about the construction of gendered identities in the music technology classroom. It explores how gendered discourses around music composition and technology are constructed and how young composers position themselves within these discursive frameworks"--Introd.
Challenging technological determinism in the music education classroom -- Gendered cultures in the music technology classroom -- Gendering technological expertise -- Gendering the musical idea -- Computers as a medium for composition -- Reclaiming compositional spaces -- Conclusion.
Includes bibliographical references (p. [139]-152) and index.
Keywords: Computer music -- Instruction and study -- Great Britain; Music -- Instruction and study -- Technological innovations; Sex differences in education -- Great Britain; Music and technology